Environmental impact evaluation of low-carbon concrete incorporating fly ash and limestone - J. Thorne; D.V. Bompa; M.F. Funari; N. Garcia-Troncoso (Cleaner Materials, 2024)
This work examines the environmental impact of low-carbon concrete that incorporates supplementary cementitious materials (SCMs). After reviewing near-zero carbon SCMs and low-carbon concrete, a life cycle assessment (LCA) was undertaken for concrete mix designs with normal-to-high compressive strengths, incorporating limestone and fly ash as cement replacements. The analysis includes relevant region-specific life cycle inventory parameters for raw materials, energy production, and transportation. A comparative assessment between embodied carbon emissions and the material mechanical performance is then made. The results of this paper indicate that incorporating limestone and fly ash in concrete can reduce carbon emissions, yet at a proportional decrease in mechanical properties compared to conventional cement concrete. The combination of cement and fly ash produced, on average, a higher strength concrete by 20.5% and lower CO2-eq values by 21.1% when compared to limestone cement blends. The CO2-eq emissions associated with transportation of the main constituents for concrete production were on average below 4% of the total CO2-eq per mix. In addition to eco-mechanical quantitative assessments, the study offers insights and recommendations for the development of concrete materials considering global resource availability of near-zero carbon concrete constituents.